ANALISA TERHADAP PUTUSAN MAHKAMAH KONTITUSI NOMOR 46/PUU-VIII/2010 MENGENAI STATUS ANAK - Darda Pasmatuti (STIH Putri Maharaja, 2017)
Marriage is a sacred part of life, because it must pay attention to norms and rules of life in society. But in reality, not everyone is so principled, with a variety of justifiable reasons that are reasonable and acceptable to society, marriage is often not appreciated for its sanctity. Marriage is a medium that will unite two people in a household. Marriage is the only unifying rite of two persons officially recognized in both state law and religious law. Problem under study is to analyze the decision of Constitutional Court Number 46/PUU-VIII/2010 regarding the status of children, in this case the research method used is descriptive research that emphasizes the data in the form of narrative and argumentation of words and not on data in the form of numbers, numbers. Using the normative juridical approach of trying to learn every legal material that is related to the subject of the study and then comparing with the rules of legislation, theories and opinions of experts on the issues discussed. Test material submitted from Hj. Aisha Mochtar to the Constitutional Court regarding the provisions of Article 2 and Article 43 paragraph (1) of Law no. 1 of 1974 concerning Marriage of Article 28 B Paragraph (1) and (2) of the 1945 Constitution relating to the Rights of the Child and Article 28 D of the 1945 Constitution relating to the right of everyone to the recognition, guarantee, protection and certainty of equitable law and equal treatment in before the law. Article 2 of Law no. 1 Year 1974, related to legitimated marriage is marriage recorded at the institution of marriage. Meanwhile, Article 43 of Law no. 1 Year 1974, related to the status of children outside marriage. The test of the material is granted in decision No. 46/PUU-VIII/2010. Which will be discussed is the Decision Analysis of the Constitutional Court. Decision 46/PUU-VIII/2010 child status.